The novel proautophagy anticancer drug ABTL0812 potentiates chemotherapy in adenocarcinoma and squamous nonsmall cell lung cancer. Issue 4 (6th February 2020) - López‐Plana, Anna; Fernández‐Nogueira, Patricia; Muñoz‐Guardiola, Pau; Solé‐Sánchez, Sònia; Megías‐Roda, Elisabet; Pérez‐Montoyo, Héctor; Jauregui, Patricia; Yeste‐Velasco, Marc; Gómez‐Ferreria, Mariana; Erazo, Tatiana; Ametller, Elisabet; Recalde‐Percaz, Leire; et al.
Abstract : Around 40% of newly diagnosed lung cancer patients are Stage IV, where the improvement of survival and reduction of disease‐related adverse events is the main goal for oncologists. In this scenario, we present preclinical evidence supporting the use of ABTL0812 in combination with chemotherapy for treating advanced and metastatic Nonsmall cell lung adenocarcinomas (NSCLC) and squamous carcinomas. ABTL0812 is a new chemical entity, currently in Phase 1b/2a clinical trial for advanced squamous NSCLC in combination with paclitaxel and carboplatin (P/C), after successfully completing the first‐in‐human trial where it showed an excellent safety profile and signs of efficacy. We show here that ABTL0812 inhibits Akt/mTOR axis by inducing the overexpression of TRIB3 and activating autophagy in lung squamous carcinoma cell lines. Furthermore, treatment with ABTL0812 also induces AMPK activation and ROS accumulation. Moreover, combination of ABTL0812 with chemotherapy markedly increases the therapeutic effect of chemotherapy without increasing toxicity. We further show that combination of ABTL0812 and chemotherapy induces nonapoptotic cell death mediated by TRIB3 activation and autophagy induction. We also present preliminary clinical data indicating that TRIB3 could serve as a potential novel pharmacodynamic biomarker to monitor ABTL0812 activity administered alone or in combination with chemotherapy in squamous NSCLC patients. The safety profile of ABTL0812 and its good synergy with chemotherapy potentiate the therapeutic potential of current lines of treatment based on chemotherapy regimens, arising as a promising option for improving these patients therapeutic expectancy. Abstract : What's new? Non‐small cell lung carcinoma is a common lung cancer with poor prognosis due to late diagnosis and frequent drug resistance of the tumor. Here the authors examined the cytotoxic effect of ABTL0812, a new AKT/mTOR inhibitor currently under clinical development, in combination with common chemotherapy regimens in lung squamous carcinoma cell lines. They demonstrate non‐apoptotic cell death mediated by activation of the Tribbles‐3 pseudokinase (TRIB3) and autophagy induction in response to ABTL0812 co‐treatment, proposingTRIB3 as a potential new biomarker to monitor the activity of ABTL0812 treatment in human clinical trials.